2018
DOI: 10.4103/abr.abr_79_18
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Diagnostic Value of Ultrasonography in Acute Appendicitis

Abstract: Background:Acute appendicitis is one of the most commonly diagnosed surgical diseases that its accurate diagnosis is still a problem, and there is no certainty. Ultrasound is recommended for diagnosis of appendicitis as an easy and noninvasive method. Therefore, due to the spread of disease and the urgent need to accurately diagnose in all educational centers, we decided to determine the diagnostic value of this inclusive method in identifying acute appendicitis.Materials and Methods:This is a descriptive cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…[15] Although USG has been shown to have more than 70% sensitivity and specificity in the diagnosis of acute appendicitis, and it has been shown to have high diagnostic accuracy in acute appendicitis, the method depends largely on the user's experience and knowledge. [16][17][18] In the study conducted by Hosseini et al, [19] the sensitivity and specificity of USG were reported as 37.1% and 87.2%, respectively, in tertiary health care centers. Due to its low negative predictive value (11.7%), USG was recommended for differential diagnosis and complicated cases of appendicitis rather than routine use.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Although USG has been shown to have more than 70% sensitivity and specificity in the diagnosis of acute appendicitis, and it has been shown to have high diagnostic accuracy in acute appendicitis, the method depends largely on the user's experience and knowledge. [16][17][18] In the study conducted by Hosseini et al, [19] the sensitivity and specificity of USG were reported as 37.1% and 87.2%, respectively, in tertiary health care centers. Due to its low negative predictive value (11.7%), USG was recommended for differential diagnosis and complicated cases of appendicitis rather than routine use.…”
Section: Discussionmentioning
confidence: 99%
“…In many prospective studies, the graded compression scanning technique has been recognized as the standard scanning technique of the appendix, with a sensitivity of 77-89%, and a specificity of 94-96% [6,13,[28][29][30][31]. This technique can be used in combination with the "mowingthe-lawn" technique using a 3.5 MHz convex probe to scan the whole abdomen, or it can be used alone, usually The "mowing-the-lawn" technique.…”
Section: Graded Compression Techniquementioning
confidence: 99%
“…In most of the cases, it is difficult to reach a definitive diagnosis. Many patients do not show the classical signs and symptoms of acute appendicitis 7 . Various other conditions result in right iliac fossa pain, especially in females, which may complicate further the process of diagnosis 1 .…”
Section: Introductionmentioning
confidence: 99%